Security And Safety Evaluation of Motorcycle Parking Mall Podomoro City (International Journal of Architecture and Urbanism, 2021)
So many cases of crime have occurred in the parking area. Because this causes many losses, ways are needed to avoid it happening again. One of the efforts that can be done in preventing the occurrence of crime in the parking area is by applying security aspects with the concept of Crime Prevention Through Environmental Design (CPTED) and applying safety aspects that examine security aspects in preventing crime in the environment of human activities in a design approach. Environmental and safety aspects. In this study, the method used is descriptive qualitative to obtain factual and systematic data. The data is processed using the AHP (Analytical Hierarchy Process) method with the help of software, namely Super Decision, to get the value of each CPTED component for motorcycle parking facilities. The value of the study of applying the CPTED concept theory for security and safety aspects in the Podomoro Mall motorcycle parking area shows that the elements of the CPTED concept and safety aspects in the motorcycle parking area have not been fully implemented. However, overall security and safety in this parking area are guaranteed because almost all the variables available at this location already meet existing standards. The riders feel safe and secure when they are in this parking area even though some aspects are not met. It could be improved would be much better. The results of this study are expected to be helpful in the field of architecture, especially in crime.